Treatment related impairments in arm and shoulder in patients with breast cancer: a systematic review. - Janine T Hidding; Carien H G Beurskens; Philip J van der Wees; Hanneke W M van Laarhoven; Maria W G Nijhuis-van der Sanden (PLoS ONE)
Background Breast cancer is the most common type of cancer in women in the developed world. As a result of breast cancer treatment, many patients suffer from serious complaints in their arm and shoulder, leading to limitations in activities of daily living and participation. In this systematic literature review we present an overview of the adverse effects of the integrated breast cancer treatment related to impairment in functions and structures in the upper extremity and upper body and limitations in daily activities. Patients at highest risk were defined. Methods and findings We conducted a systematic literature search using the databases of PubMed, Embase, CINAHL and Cochrane from 2000 to October 2012, according to the PRISMA guidelines. Included were studies with patients with stage I-III breast cancer, treated with surgery and additional treatments (radiotherapy, chemotherapy and hormonal therapy). The following health outcomes were extracted: reduced joint mobility, reduced muscle strength, pain, lymphedema and limitations in daily activities. Outcomes were divided in within the first 12 months and >12 months post-operatively. Patients treated with ALND are at the highest risk of developing impairments of the arm and shoulder. Reduced ROM and muscle strength, pain, lymphedema and decreased degree of activities in daily living were reported most frequently in relation to ALND. Lumpectomy was related to a decline in the level of activities of daily living. Radiotherapy and hormonal therapy were the main risk factors for pain. Conclusions Patients treated with ALND require special attention to detect and consequently address impairments in the arm and shoulder. Patients with pain should be monitored carefully, because pain limits the degree of daily activities. Future research has to describe a complete overview of the medical treatment and analyze outcome in relation to the treatment. Utilization of uniform validated measurement instruments has to be encouraged.